2017
DOI: 10.1016/j.trci.2017.03.005
|View full text |Cite
|
Sign up to set email alerts
|

UB‐311, a novel UBITh® amyloid β peptide vaccine for mild Alzheimer's disease

Abstract: IntroductionA novel amyloid β (Aβ) synthetic peptide vaccine (UB-311) has been evaluated in a first-in-human trial with patients of mild-to-moderate Alzheimer's disease. We describe translational research covering vaccine design, preclinical characterization, and phase-I clinical trial with supportive outcome that advances UB-311 into an ongoing phase-II trial.MethodsUB-311 is constructed with two synthetic Aβ1–14–targeting peptides (B-cell epitope), each linked to different helper T-cell peptide epitopes (UBI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
106
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(109 citation statements)
references
References 53 publications
2
106
0
1
Order By: Relevance
“…1 For clinical application, chimeric peptide vaccines composed of a B-cell epitope and T-cell epitope have been developed instead of vaccines including large carrier proteins. 2 In this study, AJP001 showed a strong affinity for the haplotype of BALB/cA mice, and the antibody-producing efficiency of the AJP001 conjugate vaccine correlated with its affinity. In addition, binding affinity for human HLA-DR was predicted, and AJP001 revealed a strong binding affinity for HLA-DR alleles that are frequently found in the Japanese population (data not shown).…”
Section: Discussionmentioning
confidence: 53%
See 3 more Smart Citations
“…1 For clinical application, chimeric peptide vaccines composed of a B-cell epitope and T-cell epitope have been developed instead of vaccines including large carrier proteins. 2 In this study, AJP001 showed a strong affinity for the haplotype of BALB/cA mice, and the antibody-producing efficiency of the AJP001 conjugate vaccine correlated with its affinity. In addition, binding affinity for human HLA-DR was predicted, and AJP001 revealed a strong binding affinity for HLA-DR alleles that are frequently found in the Japanese population (data not shown).…”
Section: Discussionmentioning
confidence: 53%
“…These B‐cell‐type peptide vaccines are required to be conjugated to large carrier proteins such as KLH . For clinical application, chimeric peptide vaccines composed of a B‐cell epitope and T‐cell epitope have been developed instead of vaccines including large carrier proteins . In this study, AJP001 showed a strong affinity for the haplotype of BALB/cA mice, and the antibody‐producing efficiency of the AJP001 conjugate vaccine correlated with its affinity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Our group has also been focusing on combining the inhibitory properties of inhibitor peptides with CPPs [362]. Peptide vaccines (reviewed by Baig et al [363] have also gained interest in the immunotherapy of different types of cancer [364] such as breast cancer [365,366] or lung cancer [367], virally mediated diseases such as influenza [368], HPV [369,370], HIV and neurodegenerative diseases [363] such as Alzheimer's [371]. These peptide vaccines are frequently delivered as emulsions with adjuvants [372] to facilitate uptake across the membrane.…”
Section: Future Perspectives: Characterizing Membrane Active Peptidesmentioning
confidence: 99%